A CFD study of coupled aerodynamic‐hydrodynamic loads on a semisubmersible floating offshore wind turbine. Issue 1 (3rd November 2017) - Tran, Thanh Toan; Kim, Dong‐Hyun
Abstract: The prediction of dynamic characteristics for a floating offshore wind turbine (FOWT) is challenging because of the complex load coupling of aerodynamics, hydrodynamics, and structural dynamics. These loads should be accurately calculated to yield reliable analysis results in the design phase of a FOWT. In this study, a high‐fidelity fluid‐structure interaction simulation that simultaneously considers the influence of aero‐hydrodynamic coupling due to the dynamic motion of a FOWT has been conducted using computational fluid dynamics based on an overset grid technique. The DeepCwind semisubmersible floating platform with the NREL 5‐MW baseline wind turbine model is considered for objective numerical verification with the NREL FAST code. A state‐of‐the‐art computational model based on the coupled computational fluid dynamics and dynamic structure analysis is constructed and analyzed to solve multiphase flow, 6 degrees of freedom motions of OC4 semisubmersible FOWT. A quasi‐static mooring solver is also applied to resolve the constraint motion of floater because of a 3‐line mooring system. The influence of tower shadow on the unsteady aerodynamic performance and loads is also demonstrated. Finally, complex unsteady flow fields considering blade and tower interference effects among blade‐tip vortices, shedding vortices, and turbulent wakes are numerically visualized and investigated in detail.